2022
DOI: 10.3390/ijms24010706
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Semi-Supervised Active Learning in Automated Wound Image Segmentation

Abstract: Appropriate wound management shortens the healing times and reduces the management costs, benefiting the patient in physical terms and potentially reducing the healthcare system’s economic burden. Among the instrumental measurement methods, the image analysis of a wound area is becoming one of the cornerstones of chronic ulcer management. Our study aim is to develop a solid AI method based on a convolutional neural network to segment the wounds efficiently to make the work of the physician more efficient, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…In this work, we developed an ad hoc Active Semi-Supervised Learning (ASSL) strategy, reproducing the procedure already discussed in our previous work [ 23 ]. The ASSL procedure was reiterated for several rounds of training, requiring the clinicians to simply accept or discard the output of the model after each round.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In this work, we developed an ad hoc Active Semi-Supervised Learning (ASSL) strategy, reproducing the procedure already discussed in our previous work [ 23 ]. The ASSL procedure was reiterated for several rounds of training, requiring the clinicians to simply accept or discard the output of the model after each round.…”
Section: Methodsmentioning
confidence: 99%
“…The validated images (and corresponding segmentation masks) which satisfied all the criteria were inserted into the training set as the starting point of the current ASSL training strategy. Ad hoc software was developed to minimize the time required for the validation procedure [ 29 ]. The validation was performed, reviewing the segmentations overlayed on the original image displayed on a high-resolution screen and without limits of time for the evaluation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Curti et al [ 2 ] suggested an automated model able to perform a deep analysis of wounds from images acquired from smartphones using an app developed ad hoc . This method is based on an active semi-supervised learning training of a convolutional neural network.…”
mentioning
confidence: 99%